Perspectives for solid biopolymer electrolytes in dye sensitized solar cell and battery application. (November 2016) - Singh, Rahul; Polu, Anji Reddy; Bhattacharya, B.; Rhee, Hee-Woo; Varlikli, Canan; Singh, Pramod K.
Abstract: Photovoltaic technologies represent one of the leading research areas of solar energy which is one of the most powerful renewable alternatives of fossil fuels. In a common photovoltaic application the batteries play a key role in storage of energy generated by solar panels. Although it will take time for dye sensitized solar cells (DSSCs) and batteries based on biopolymer electrolytes to take their places in the market, laboratory studies prove that they have a lot to offer. Most efficient DSSCs and batteries available in market are based on liquid electrolytes. The advantages of liquid electrolytes are having high conductivity and good electrode-electrolyte interface whereas, disadvantages like corrosion and evaporation limit their future sustainability. Biopolymer electrolytes are proposed as novel alternatives which may overcome the problems stated above. In this review, we focus on fabrication, working principle as well as up to date status of DSSCs and batteries using biopolymer electrolytes. The effects of structural and electrical properties of biopolymer based electrolytes on the solar energy conversion efficiencies of DSSCs and their compatibility with lithium or other salts in battery applications are summarized. Biopolymer electrolyte based DSSCs are categorized on the basis of types of additives and recent outcomes of author's laboratory studies on biopolymer electrolyte based DSSCs and batteries are also presented.